Characteristics of women with ischemic sudden cardiac death - Hookana, I.; Holmström, L.; Eskuri, M. A. E.; Pakanen, L.; Ollila, M. M.; Kiviniemi, A. M.; Kenttä, T.; Vähätalo, J.; Tulppo, M.; Lepojärvi, E. S.; Piltonen, T.; Perkiömäki, J.; et al. (Annals of medicine (Helsinki), 2023)
Sudden cardiac death (SCD) is a significant mode of death causing 15-20% of all deaths in high-income countries. Coronary artery disease (CAD) is the most common cause of SCD in both sexes, and SCD is often the first manifestation of underlying CAD in women. This case-control study aimed to determine the factors associated with SCD due to CAD in women.BACKGROUNDSudden cardiac death (SCD) is a significant mode of death causing 15-20% of all deaths in high-income countries. Coronary artery disease (CAD) is the most common cause of SCD in both sexes, and SCD is often the first manifestation of underlying CAD in women. This case-control study aimed to determine the factors associated with SCD due to CAD in women.The study group consisted of women with CAD-related SCD (N = 888) derived from the Fingesture study conducted in Northern Finland from 1998 to 2017. All SCDs underwent medicolegal autopsy. The control group consisted of women with angiographically verified CAD without SCD occurring during the 5-year-follow-up (N = 610). To compare these groups, we used medical records, autopsy findings, echocardiograms, and electrocardiograms (ECGs).METHODSThe study group consisted of women with CAD-related SCD (N = 888) derived from the Fingesture study conducted in Northern Finland from 1998 to 2017. All SCDs underwent medicolegal autopsy. The control group consisted of women with angiographically verified CAD without SCD occurring during the 5-year-follow-up (N = 610). To compare these groups, we used medical records, autopsy findings, echocardiograms, and electrocardiograms (ECGs).Subjects with SCD were older (73.2 ± 11.3 vs. 68.8 ± 8.0, p < 0.001) and were more likely to be smokers or ex-smokers (37.1% vs. 27.6%, p = 0.045) compared to control patients. The proportion of subjects with prior myocardial infarction (MI) was higher in controls (46.9% vs. 41.4% in SCD subjects, p = 0.037), but in contrast, SCD subjects were more likely to have underlying silent MI (25.6% vs. 2.4% in CAD controls, p < 0.001). Left ventricular hypertrophy (LVH) was more common finding in SCD subjects (70.9% vs. 55.1% in controls, p < 0.001). Various electrocardiographic abnormalities were more common in subjects with SCD, including higher heart rate, atrial fibrillation, prolonged QTc interval, wide or fragmented QRS complex and early repolarization. The prevalence of Q waves and T inversions did not differ between the groups.RESULTSSubjects with SCD were older (73.2 ± 11.3 vs. 68.8 ± 8.0, p < 0.001) and were more likely to be smokers or ex-smokers (37.1% vs. 27.6%, p = 0.045) compared to control patients. The proportion of subjects with prior myocardial infarction (MI) was higher in controls (46.9% vs. 41.4% in SCD subjects, p = 0.037), but in contrast, SCD subjects were more likely to have underlying silent MI (25.6% vs. 2.4% in CAD controls, p < 0.001). Left ventricular hypertrophy (LVH) was more common finding in SCD subjects (70.9% vs. 55.1% in controls, p < 0.001). Various electrocardiographic abnormalities were more common in subjects with SCD, including higher heart rate, atrial fibrillation, prolonged QTc interval, wide or fragmented QRS complex and early repolarization. The prevalence of Q waves and T inversions did not differ between the groups.Underlying LVH and previous MI with myocardial scarring are common and often undiagnosed in women with CAD-related SCD. These results suggest that untreated CAD with concomitant myocardial disease is an important factor in SCD in women.CONCLUSIONSUnderlying LVH and previous MI with myocardial scarring are common and often undiagnosed in women with CAD-related SCD. These results suggest that untreated CAD with concomitant myocardial disease is an important factor in SCD in women.